AB0320 Rheumatoid arthritis in brazil – the "real" study: a nationwide prospective study. (15th June 2017) - Castelar-Pinheiro, G; Vargas-Santos, AB; Albuquerque, C; Amorim, R; Giorgi, R; Radominski, S; Pereira, I; Guimarães, MF; Bértolo, M; Louzada, P; Cunha, MF; Bonfiglioli, K; et al.
Abstract : Background: Early diagnosis and immediate treatment are critical in achieving optimal outcomes in rheumatoid arthritis (RA). However, anecdotal evidence suggests that in Brazil there is still a significant delay in patient referral, RA diagnosis and DMARD initiation. The lack of national data hinders effective advocacy for proper public health policies, which led the RA commission of the Brazilian Society of Rheumatology to create a nationally-representative multicenter RA cohort to provide the necessary data. Objectives: To describe the development process and baseline characteristics of a large, nationally-representative multicenter cohort of RA patients in Brazil. Methods: Eleven public rheumatology centers from all of the 5 regions of Brazil enrolled ∼100 consecutive RA patients each (1987 ARA or 2010 ACR-EULAR). This cohort is being followed prospectively for 1 year, with systematic data collection at time 0, 6±1 months and 12±1 months, and registration of all other visits during this 1-year period. Data collection began in 08–2015, using a single online electronic medical record, and included demographic, socioeconomic, clinical, lab, radiographic and therapeutic characteristics, along with functional status, quality of life and adherence to treatment information. Results: 1125 patients were enrolled (Table), ∼90% were female, with a mean age of 56 years and median disease duration of 13 years. Median BMI was 27 kg/m 2, with 64% of the patients classified as overweight or obese. The interval between symptoms and diagnosis varied from 1 to 457 months (median 12 months). Almost half of the patients were on glucocorticoids, 96% on DMARDs, with 36% on biologics. Only 7% were seronegative for both rheumatoid factor and ACPA. Median HAQ-DI was 0.875 and median DAS28-ESR was 3.5, with 58.6% of patients presenting moderate or high disease activity. Conclusions: The delay in diagnosis may explain the high percentage of patients with moderate or high disease activity and erosive disease. The low level of physical dysfunction observed in this established, predominantly seropositive RA population may be explained by the large proportion of patients on glucocorticoid and biologic therapy. Our findings suggest that, despite current treatment concepts being well known and accepted by Brazilian rheumatologists, there is still a gap in early diagnosis and management of RA. Disclosure of Interest: None declared